The effectiveness of LKPD Based on Discovery Learning to Improve Collaboration Skills and Mastery of Student Concepts - Siti Nurjanah; Ratu Betta Rudibyani; Emmawaty Sofya (Universitas Lampung, 2020)
This research was done to describe the effectiveness of using LKPD based on discovery learning to improve students collaboration skill and concepts mastery of the material equation of the rate and reaction order. A quasi experimental was used in this research which the design is a pretest-posttest control group design. The sample in this research was XI MIPA 1 as an experimental class and XI MIPA 2 as a control class, it was taken with a purposive sampling technique. The improvement of the students can be seen from the average n-Grain scores and based on effect size of collaboration skill and concept mastery through LKPD based on discovery learning. The results showed that the n-Grain scores of collaboration skill and concept mastery through LKPD based on discovery learning improved significantly with conventional learning. It can be concluded that students collaboration skil and concept mastery of the material equation of the rate and reaction order through LKPD based on discovery learning is effective. Besides, another result of LKPD based on discovery learning showed that there was a moderate in students collaboration skill and there was a huge in students of concept mastery.Keywords: the effectiveness, LKPD based discovery learning, collaboration skills, mastery of concepts.